Beyond gender-blind climate action: a participatory framework for inclusive climate-smart agriculture - Zijun Shen; Tufa Chen; Huang Liu (Emerald Publishing, 2025)
Abstract PurposeThe purpose of this study aims to identify gender-differentiated climate risks and access to resources; participatory rank of CSA practices by gender and agro-ecology; and link priorities to economic indicators to be scaled to action.Design/methodology/approachThe authors used the Climate Risk and Vulnerability (CRV) appraisal, which is a combination of participatory rural appraisal (PRA), rapid rural appraisal (RRA), focus groups and household survey, in Gulu, Uganda (n = 50 households) and Kilolo, Tanzania (n = 50 households) between March and October 2014.FindingsThis data is then subjected to extensive analysis, triangulation and validity. When applied to data from Tanzania and Uganda, the CRV shows that various social groupings (based on gender) and agricultural ecological regions exhibit varied levels of vulnerability, restrictions and CSA goals at different locations. Stakeholders may target and execute CSA while simultaneously considering biophysical, social and economic problems through the CRV.Originality/valueResource mapping, climate and historical calendars, cropping calendars, organization mapping, transect walks, key informant interviews, farmer interviews and a pairwise ranking matrix are all part of the CRV methodology, which integrates frequent PRA and RRA instruments into a single system that separates the gender scale.
Keywords: Climate-smart agriculture; Gender scale; Participatory rural appraisal; Rapid rural appraisal